GSB PARTICIPATES IN COMMUNITY SERVICE AT TELUK BAHANG - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 7 May 2016 Approximately 50 Master of Business Administration (MBA) students along with the lecturers and staff of the Graduate School of Business (GSB) Universiti Sains Malaysia (USM) participated in the community service programme ‘GSB@USM (mailto:GSB@USM): Nurturing Business Sustainability’ at Teluk Bahang, Penang recently.